RESPON PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) VARIETAS VIMA 4 AKIBAT PEMBERIAN KOMBINASI PUPUK P, K DAN CENDAWAN MIKORIZA ARBUSKULAR (CMA) - Novien, Alienda; Jaenudin, Amran; Faqih, Achmad (Prodi Agronomi Pascasarjana Universitas Swadaya Gunung Jati, 2023)
The aims of this study is to determine the best response of mung bean to the application of a combination of phosphorus, potassium and arbuscular mycorrhizal fertilizers, to determine the significant correlation between growth components and yield component to yield of mung bean (Vigna radiata L.) Vima 4. The research was carried out from August to October 2021 at the Ma'had Al Zaytun Agicultural, Indramayu, West Java. The location is ± 50 m above sea level, type of soil is latosol with pH of 6.11 and a clay texture (67.96 %). Rainfall is 73 mm/month and air temperature is 32 0C. The research method uses an experimental method with a combination randomized block design. There were 9 combinations of SP-36, KCl and Arbuscular Mycorrhizal Fungi (AMF) treatments. SP-36 fertilizer consisted of 3 levels 50, 75 and 100 kg/ha, KCl fertilizer with 3 levels 50, 75 and 100 kg/ha and CMA with 3 levels 5, 10 and 15 kg/planting hole. Each combination was repeated three times, 27 experimental plots. Each experimental plot is 4 m2. Observation data were processed using analysis of variance, Scott-Knott further test and Pearson Product Moment correlation test. The results showed that (1) the combination of P, K and CMA treatments had a significant effect on root volume at 35 DAP, number of pods per plant, pod weight per plant, pod weight per plot, seed weight per plant, and seed weight per plot. significant effect on plant height, number of leaves, leaf area index, number of branches and plant growth rate; (2) treatment of 75 kg SP36/ha, 75 kg KCl/ha, and CMA 15 g/hole gave the highest seed weight of 546.31 g/plot (1.16 tons/ha) but not significantly different from the treatment of 50 kg SP36 /ha, 50 kg KCl /ha, and CMA 15 g/hole which yielded grain weight of 484.89 g/plot (1.03 tons/ha); (3) there was a significant correlation between root volume at 35 DAP and the number of pods per plant to seed weight per plot